Answer:
12a + 24 = 6(2a + 4) is the equivalent expressions
Step-by-step explanation:
Given the terms ; 4, 12a, 6, 2a, and 24
There are two terms with unknown = 12a and 2a
but 12a = 2a x 6 .........(1)
from the last term = 24 = 6 x 4 ...........(2)
add both equation 1 and 2 = 12a + 24
12a + 24 = 6(2a + 4) is the equivalent expressions .
to VERIFY; Use a = 2
substitute into the expression ; LHS = RHS
= 12(2) + 24 = 24 + 24 = 48 (LHS)
FOR RHS = 6(2a+4) = 6(2x2 + 4)
= 6(4+4) = 48
Hence LHS = RHS
It would be: - 2 - (-10) = 5x - 12
= -2 + 10 = 5x - 12
= 8 + 12 = 5x
= x = 20 / 5
= x = 4
Answer:
c
Step-by-step explanation:
Answer:
5m-n-4p
4a^2+6x-3
Step-by-step explanation:
3m-4n +7p
-5m +9n -6p
+7m -6n -5p
----------------------
Combine like terms
3m-4n +7p
-5m +9n -6p
+7m -6n -5p
----------------------
(3-5+7)m +(-4+9-6)n +(7-6-5)p
5m-n-4p
a^2 -3x +1
a^2 +9x -6
2a^2 +0x +2
----------------------
Combine like terms
a^2 -3x +1
a^2 +9x -6
2a^2 +0x +2
----------------------
(1+1+2)a^2 +(-3+9+0)x +(1-6+2)
4a^2+6x-3
Answer:
<h2>
<u><em>its B</em></u></h2>
Step-by-step explanation: